Factors affecting population fluctuations of the glacial relict amphipod Monoporeia affinis (Lindstrom) in Sweden's largest lakes - Goedkoop, Willem; Johnson, Richard (SPRINGER, 2001)
Factors affecting long-term (1982-2000) population densities of the glacial relict amphipod Monoporeia affinis were studied in Sweden's three largest lakes. Monoporeia showed large population fluctuations in all three lakes, with conspicuous peaks in density occurring in Lakes Vanern and Malaren. In Lake Vanern, amphipod densities showed highly significant relationships with spring maximum diatom biovolume at a 1-yr lag. The lack of relationship between diatom biovolumes and Monoporeia densities in L. Vattern is likely due to the larger depth and the lower nutrient content of this lake. In eutrophic L. Malaren, summer hypoxia (<4 Mg O-2 L-1) is likely an important regulating factor. Hypolimnetic temperature showed a clear periodicity with relatively warm deep water occurring between 1989 and 1994. Hypolimnetic temperatures in Vanern and Vattern were correlated with total solar irradiance. However, neither hypolimnetic water temperature nor diatom biovolumes correlated with the North Atlantic Oscillation winter index. We speculate that variations in temperature and near-bottom oxygen concentrations negatively affect population densities by acting on recruitment success (reproduction) and juvenile (young-of-the-year) survival.